Service satisfaction and utilization among sexual assault survivors seeking assistance at the Rape Trauma Service in Reykjavik Iceland - Bryndís Lóa Jóhannsdóttir 1990- (2016)
Sexual violence is a serious public health problem that has resulted in the establishment of professional, multidisciplinary service centers for victims in most of the Nordic countries. In Iceland a Rape Trauma Service (RTS) was established in 1993. The RTS is a multidisciplinary service clinic that provides free comprehensive and immediate 24 hour service to all sexually victimized adolescents and adults. In addition to acute medical, forensic, legal and psychological services the clinic offers follow-up psychological services due to the potential severe psychological consequences of sexual assault. According to research a big proportion of sexual assault survivors do not utilize the available service after trauma, even though the trauma can have very serious consequences for the survivor, the most common one being PTSD. The purpose of this study was to examine survivors’ views of the RTS services and in particular the follow-up psychological services, as well as reasons for not accepting psychological services. Furthermore, the goal was to examine the relationship between the initial post assault psychological symptoms (depressive symptoms, posttraumatic stress symptoms) and service utilization as well as survivors’ views of the RTS services and service. The participants of the study were 91 female survivors who had sought the RTS services in the years 2010 to 2014 and agreed to participate in a service satisfaction survey. Three levels of follow-up psychological services at the RTS were defined: psychological first aid, follow-up psychosocial support and cognitive processing therapy (CPT). The results indicated that most survivors were happy with the RTS services and would recommend it to others. The most common reason given for not accepting or utilizing the follow-up psychological services were e.g. “I wasn’t ready to face what happened” and “The service was too far away from my home” which were categorized as avoidance. Those participants who utilized the follow-up psychological service described a desire ...